Associations between dietary mycotoxins exposures and risk of hepatocellular carcinoma in a European cohort. - Inge Huybrechts; Inarie Jacobs; Carine Biessy; Elom K Aglago; Mazda Jenab; Liesel Claeys; Jiri Zavadil; Corinne Casagrande; Genevieve Nicolas; Ghislaine Scelo; Andrea Altieri; Beatrice Fervers; et al. (PLoS ONE)
Mycotoxins have been hypothesized to contribute to a diversity of adverse health effects in humans, even at low concentrations. Certain mycotoxins are established human carcinogens, whereas for others research suggests potential carcinogenic effects. The aim of this study was to determine the association between dietary exposure to mycotoxins and hepatobiliary cancers in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. EPIC questionnaire data were matched to mycotoxin food occurrence data compiled by the European Food Safety Authority to assess long-term dietary mycotoxin exposure (expressed as μg/kg body weight/day) and then relate them to the risk of hepatocellular carcinoma (HCC) (n = 255) and biliary tract cancers (n = 273). Analyses were conducted using multivariable Cox proportional hazards regression models to compute hazard ratios (HR) and 95% confidence intervals (95% CI). Key food groups contributing to mycotoxin exposure were cereals and cereal-based products, vegetables, non-alcoholic beverages (including fruit juices) and fruits. Estimated intake of deoxynivalenol (DON) and its derivatives was positively associated with HCC risk (HRT3vsT1: 1.90, 95% CI: 1.18-3.05, p-trend <0.01). No statistically significant associations were found for the other mycotoxins. Further research to confirm our observations and investigate potential underlying mechanisms of these compounds is warranted. These data may provide evidence of HCC risks associated with higher dietary intake levels of DON, which has not yet been classified as a human carcinogen.